Nonlinear growth of zinc tin oxide thin films prepared by atomic layer deposition. Issue 16 (15th August 2021) - Gu, Yang; Tao, Jia-Jia; Wang, Tao; Liu, Yu-Hang; Peng, Bo-Fang; Zhu, Li-Yuan; Lu, Hong-Liang
Abstract: Zinc tin oxide (ZTO) thin films can be deposited by atomic layer deposition (ALD) with adjustable electrical, optical and structural properties. However, the ternary ALD processes usually suffer from low growth rate and difficulty in controlling film thickness and elemental composition, due to the interaction of ZnO and SnO2 processes. In this work, ZTO thin films with different Sn levels are prepared by ALD super cycles using diethylzinc, tetrakis(dimethylamido)tin, and water. It is observed that both the film growth rate and atom composition show nonlinear variation versus [Sn]/([Sn]+[Zn]) cycle ratio. The experimental thickness measured by spectroscopic ellipsometry and X-ray reflectivity are much lower than the expected thickness linearly interpolated from pure ZnO and SnOx films. The [Sn]/([Sn]+[Zn]) atom ratios estimated by X-ray photoelectron spectroscopy have higher values than that expected from the cycle ratios. Hence, to characterize the film growth behavior versus cycle ratio, a numerical method is proposed by simulating the effect of reduced density and reactivity of surface hydroxyls and surface etching reactions. The structure, electrical and optical properties of ZTO with different Sn levels are also examined by X-ray diffraction, atomic force microscope, Hall measurements and ultraviolet–visible–infrared transmittance spectroscopy. The ZTO turns out to be transparent nanocrystalline or amorphous films with smooth surface. With more Sn contents, the film resistivity gets higher (>1 Ω cm) and the optical bandgap rises from 3.47 to 3.83 eV.